Chief Justice Rose Bird's State of the Judiciary Address at State Bar Annual Meeting - Watkins, Howard::::::::: (1985)
Toby Rothschild, Executive Director of Legal Aid of Long Beach and Linda Evans, Charles Houston Bar Association in Oakland